At-Tahawwul fī Turuqi At-Tafsīr: Min Al-Qirā’ah At-Taqlīdiyyaħ Wa Syibhi Al-Qirā’aħ At-Taqlīdiyyah Ilā Al-Qirā’aħ At-Tārikhiyyaħ Al-Maqāsidiyyaħ: التحول في طرق التفسير: من القراءة التقليدية وشبه القراءة التقليدية إلى القراءة التارخية المقاصدية - Aditya, Muhamad Anwar; Fuadi, Muhammad Azhar; Bachtiar, Maulana Yusuf (ZAD Al-Mufassirin, 2023)
This paper aims to find out the design of Islamic discourse that is relevant to the progress of science without ignoring the encounter between the three types of interpretation in the Qur'an, namely qiraah taqlidiyyah (Textual and Semi-Textual) and Tarikhiyyah-maqasidiyyah (Contextual), this qualitative research uses a literature study method with data sources are books and journal articles and other relevant sources. This research produces a relevant Islamic discourse design to prove that the Quran is a holy book for all mankind that is relevant in all places and times. However, in order to understand the context of the verse, a complete understanding of the text of the Quranic verse is also needed, so that the understanding of the verse is not separated from the original purpose of the Quran itself.